Numerical Solution of a Fractional-Order Predator-Prey Model with Prey Refuge and Additional Food for Predator - Satriyantara, Rio; Suryanto, Agus; Hidayat, Noor (Graduate School, Universitas Brawijaya, 2018)
In this paper, a fractional-order predator-prey model with prey refuge and additional food for predator is solved numerically. For that aim, the model is discretized using a piecewise constant arguments. The equilibrium points of the discrete fractional-order model are investigated. Numerical simulations are conducted to see the stability of each equilibrium point. The numerical simulations show that stability of the equilibrium points is dependent on the time step.Keywords: Additional Food, Fractional-Order, Predator-Prey, Prey Refuge.